Incremental Static Analysis for the Seismic Performance Evaluation of a Peruvian R.C. Building - Mamani, Ivan (2025)
In the present study, the incremental static or pushover analysis will be used, since it offers more accurate results compared to the linear analysis. Therefore, its application is indispensable for the evaluation of the seismic performance of a reinforced concrete structure composed of beams, columns and walls. This structure is a multi-family building of 6 levels, rectangular in shape with an area of 120 m2. The methodology used allows obtaining the capacity of the structure against applied lateral loads, thus determining the performance levels for each level of seismic hazard according to the VISION 2000 guidelines. The study begins with an exhaustive analysis of the geometry, structural elements of the building, the use of standards and guidelines related to seismic resistance. However, two 3D structural models were created in Etabs V.21, called model 1 and model 2. In model 1, the non-linear model of plastic hinges for beams and columns will be taken into account, taking into consideration that the walls are hinged with fiber type hinges. On the other hand, for model 2, the nonlinear model of fiber-type hinges for columns, beams and walls will be taken into account. However, the indispensable resource is the ASCE 41-17/23 standard for the model with plastic hinges. On the other hand, we use the constitutive models of Mander and Park to define the behavior of concrete and steel in each fiber division. Then, the results of the capacity curve in each X and Y direction are compared. Finally, the pushover curve is sectorized to obtain the performance levels for frequent, occasional, rare and very rare earthquakes. Therefore, the findings in this article are useful for professionals engaged in structural engineering who are interested in the performance evaluation of a reinforced concrete structure or in other infrastructures that exist at the international level.